Protective Effect of Red Fruit Oil (Pandanus conoideus Lam.) on Histopathological Levels of Liver Inflammation in Mice (Mus musculus) Exposed to Lead - Lina Aderia Putri; Novarina Sulsia Ista'In Ningtyas; Alfiana Laili Dwi Agustin (Universitas Airlangga, 2023)
Background: There is an increase in pollution in the environment, and plumb is one of them. Exposure to plumbum is known to induce excessive production of Reactive Oxygen Species (ROS) and result in oxidative stress at the cellular level. Oxidative stress can cause disturbances in body organs, one of which is the liver organ. Purpose: To determine the effect of giving red fruit oil as protection against plumbum exposure at the level of inflammatory cells of the mice’s liver. Method: This study was conducted for 14 days with 4 treatments, namely P0 (negative control), P1 (positive control given plumbum exposure at a dose of 0.011mg), P2 (0.3 ml of red fruit oil and plumbum exposure at a dose of 0.011mg) and P3 (0.8 ml of red fruit oil and plumbum exposure at a dose of 0.011mg). Determination of inflammatory cells in the liver of mice is carried out by looking at the HE preparation of mice’s liver under a microscope with a magnification of 400x. Results: Based on the results, it was found that there was no noticeable difference after the SPSS test on the P1, P2, and P3 treatments. Conclusion: The application of red fruit oil as a protectant to mice exposed to plumbum does not affect the level of inflammatory cells.